Diethyl aminoethyl hexanoate (DA-6) and planting density optimize soybean growth and yield formation in maize–soybean strip intercropping - Kai Luo; Xiaoting Yuan; Kejing Zhang; Yuanyuan Xue; Zhidan Fu; Ping Lin; Yiling Li; Yuze Li; Tian Pu; Xintong Qi; Yang Li; Xiaochun Wang; et al. (Crop Journal)
The exogenous plant growth regulator, diethyl aminoethyl hexanoate (DA-6), in combination with suitable varieties and planting densities, is important to increase yield in the maize–soybean strip intercropping system. To identify the role of DA-6 in mitigating high-density stress and increasing yield, we conducted a two-year field experiment examining changes in branching architecture and other yield traits of soybeans in maize–soybean strip intercropping systems. In the planting system, two soybean cultivars (ND: Nandou 25 and QH: Qihuang 34) were grown under three planting densities (D1: 102,000 plants ha−1, D2: 130,000 plants ha−1, D3: 158,000 plants ha−1) with DA-6 treatments (DA0: water control; DA60: 60 mg L−1; DA100: 100 mg L−1). Applying DA-6 at 60 mg L−1 at the fourth trifoliolate leaf stage increased soybean yield, with QH yield rising by 22.4% and 29.5% at D3 density, and ND yield by 29.5% and 30.0% at D2 density in 2022 and 2023, respectively, compared with D1 under DA0. DA-6 improved photosynthesis in both varieties under D2 density, with DA60 increasing ND canopy photosynthetic rate by 15.1%–16.4% and QG by 9.1%–20.6% over two years. In ND, DA-6 enhanced branching, raising the leaf area index by 37%, branch number from 3.6 to 4.7 per plant, and total pod number by 19.7%. In QH, yield grains were mainly due to a 17% increase in the number of stem pods and a 6.5% improvement in hundred-grain weight. In the maize–soybean strip intercropping system, QH achieved a high yield by forming a high-density (D2 to D3) main stem pod, and ND by combining moderate density (D1 to D2) with DA-6-induced branching.